Distribution of EML4-ALK fusion variants and clinical outcomes in patients with resected non-small cell lung cancer. (November 2020) - Tao, Hong; Shi, Liang; Zhou, Aoxue; Li, Hongxia; Gai, Fei; Huang, Zhan; Che, Nanying; Liu, Zhe
Graphical abstract: Highlights: Gene profiles and prognosis were explored in EML4 - ALK fusion positive resectable NSCLC. Variant 1 was the predominant variant type in EML4-ALK fusion, followed by variant 3. TP53 was the most common coexisting mutation gene. Advanced T stage and EML4-ALK variant 3 were associated with shorter DFS. Abstract: Objectives: The molecular profiles and prognosis of anaplastic lymphoma kinase ( ALK ) fusion and resectable non-small cell lung cancer (NSCLC) remain unclear. This study aimed to explore the distribution of ALK fusion variants and prognostic factors in patients with surgically resected NSCLC. Material and methods: Among the 93 ALK positive surgical patients screened by immunohistochemistry (IHC) or real-time polymerase chain reaction (RT-PCR), 63 patients were confirmed as ALK rearrangement by next-generation sequencing (NGS), including 55 cases of stage I-III and 8 cases of stage IV. Medical records were retrospectively reviewed, the distribution of ALK fusion variants and prognostic factors were analyzed. Results: All of the 55 early stage patients were histological adenocarcinoma. No other fusion types were found except for echinoderm microtubule-associated protein-like 4- anaplastic lymphoma kinase ( EML4-ALK ). EML4-ALK variant 1 (E13:A20; 25/55, 45.5 %) was the predominant variant type, followed by EML4-ALK variant 3 (E6:A20; 19/55, 34.5 %) and variant 2 (E20:A20; 8/55, 14.5 %). Concomitant mutations occurred in 22 patients (22/55, 40.0 %), which involved in 32 co-mutations from 12 kinds of mutated genes. TP53 mutations were most common in coexisting mutations (13/32, 40.6 %). TP53 mutations were less frequently occurred in variant 1 group (3/25, 12.0 %) than in non-variant 1 group (10/30, 33.3 %, P = 0.064). The median disease-free survival (DFS) of the 55 patients was 22.1 months, and the median overall survival (OS) was not mature at the time of analysis. Multivariable analysis showed that stage T3 and EML4-ALK variant 3 were independent prognostic factors for shorter DFS. Neither TP53 mutations nor any coexisting mutations were related to prognosis. Conclusions: This study illustrated the patterns of EML4-ALK fusion variants and gene profiles in patients with resected NSCLC. Advanced T stage and EML4-ALK variant 3 were associated with worse prognosis. The role of TP53 mutations in prognosis is worthy of further study.